Distance to the anal verge is associated with pathologic complete response to neoadjuvant therapy in locally advanced rectal cancer. Issue 5 (19th September 2016) - Patel, Sunil V.; Roxburgh, Campbell S.; Vakiani, Efsevia; Shia, Jinru; Smith, J. Joshua; Temple, Larissa K.; Paty, Philip; Garcia‐Aguilar, Julio; Nash, Garrett; Guillem, Jose; Wu, Abraham; Reyngold, Marsha; et al.
Abstract : Background and Objectives: Achieving a pathologic complete response (pCR) after neoadjuvant therapy has been associated with better prognosis in rectal cancer patients. The objective of this study was to investigate the relationship between distance to the anal verge (DTAV) and pCR. Methods: Review of a prospectively maintained database of patients with locally advanced rectal cancer who received neoadjuvant treatment was completed. Uni‐ and multivariate analysis assessed the association between DTAV and pCR after neoadjuvant therapy. Results: Of 827 included patients, 20% had a pCR. We found that pCR rates were 11% for tumors <4 cm, 24% for tumors 4–6 cm, 30% for tumors at 6–8 cm, 17% for tumors 8–10 cm, and 14% for tumors >10 cm from the anal verge ( P = 0.002). Multivariate analysis also showed a strong association between DTAV and pCR ( P = 0.008). The bimodal distribution of pCR resulted in a lower odds ratio of pCR for tumors <4 and >8 cm from the anal verge. Conclusions: Patients with low tumors (<4 cm) and higher tumors (>8 cm), were less likely to have a pCR. Further investigation is warranted to determine if these observations are related to tumor biology or possibly differences in radiation technique. J. Surg. Oncol. 2016;114:637–641 . © 2016 Wiley Periodicals, Inc.